2014
DOI: 10.1007/s11606-014-2877-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hospital and Emergency Department Utilization by Individuals with Recent Criminal Justice Involvement: Results of a National Survey

Abstract: BACKGROUND: Individuals involved with the criminal justice system have increased health needs and poor access to primary care. OBJECTIVE: To examine hospital and emergency department (ED) utilization and related costs by individuals with recent criminal justice involvement. DESIGN: Cross-sectional survey. PARTICIPANTS: Non-institutionalized, civilian U.S. adult participants (n=154,356) of the National Survey on Drug Use and Health (2008-2011). MAIN MEASURES: Estimated proportion of adults who reported past yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…A recent seminal study found high utilization of ED and hospitalization from a national survey of individuals with recent criminal justice involvement, but did not examine PLWHA. 67 During the immediate and destabilizing post-release period, the same vulnerabilities and behaviors (high rates of SUDs, comorbid psychiatric conditions) that lead to ED visits may also correlate with recidivism. 9,35 Re-incarceration among PLHWA leaving the CJS is well-documented: among PLHWA released from prisons in Texas, annualized recidivism was 20.5 %.…”
Section: Discussionmentioning
confidence: 99%
“…A recent seminal study found high utilization of ED and hospitalization from a national survey of individuals with recent criminal justice involvement, but did not examine PLWHA. 67 During the immediate and destabilizing post-release period, the same vulnerabilities and behaviors (high rates of SUDs, comorbid psychiatric conditions) that lead to ED visits may also correlate with recidivism. 9,35 Re-incarceration among PLHWA leaving the CJS is well-documented: among PLHWA released from prisons in Texas, annualized recidivism was 20.5 %.…”
Section: Discussionmentioning
confidence: 99%
“…Multistage area probability sampling methods are used to select a representative sample of the U.S. civilian, non-institutionalized population aged 12 years or older for participation. Although the NSDUH does not sample participants from correctional facilities, it has been shown to be a useful dataset to study a variety of criminological and criminal justice topics (see Booth et al, 2013; Frank et al, 2014; Salas-Wright et al, 2015; Vaughn et al, 2014, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…2,3 Although most studies of justiceinvolved individuals do not include all of these subgroups, existing evidence suggests that approximately 70 % of justiceinvolved individuals have a substance use disorder (SUD) or mental health issue. [4][5][6][7] Yet, treatment among individuals with recent justice involvement has historically been inadequate due to lack of health insurance coverage [8][9][10] and other barriers to care, including troubles navigating the healthcare system post release, 11 disruption of medication during incarceration, 12 and lack of behavioral health services. 13 Roughly half of justice-involved individuals are expected to be eligible for health insurance through the Affordable Care Act (ACA), 10,14 and many believe insurance expansion offers an opportunity to improve access to substance abuse and mental health treatment for this population.…”
Section: Introductionmentioning
confidence: 99%